CRYSTALLIZATION AND CHARACTERIZATION OF CHROMIUM-CONTAINING SILICALITE-1 - Hari Sutrisno; Endang Dwi Siswani; Susila Kristianingrum; Suharto Suharto (Indonesian Journal of Chemistry, 2005)
Chromium-containing silicalite-1, designed CrS-1, was synthesized by the hydrothermal method and characterized by XRD and FTIR techniques. The objectives of the research are to study the synthesis of CrS-1 and investigate the effect of crystallization temperatures and times toward its character. All samples of CrS-1 crystallized in orthorhombic structure and Pnma space group. The phase observed in the XRD patterns of CrS-1 synthesized from 150 to 190 oC for 11 days showed only MFI-type phase. The CrS-1 prepared under static condition for 1 day at 150 oC indicated α-SiO2 phase, on the contrary, the samples conditioned for 2 to 8 days at 150 oC are only MFI phase.